Pruning Landscape Trees and Shrubs - Edward F. Gilman; Robert J. Black (EDIS, 2005)
The objective of this document is to present pruning techniques for Florida trees, shrubs and palms. The need for pruning, timing, types of pruning, tree pruning, shrub pruning and tools are discussed separately. Specific examples will support the pruning concepts. This document is Circular 853 (MG087), Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. This document supersedes The Woody Ornamentalist, Vol. 14, No. 7 (published July 1989) and Special Series #2, SS-ORH-902, both titled Pruning Ornamental Trees and Shrubs. This information supports Environmental Landscape Management, i.e., landscape design and management for environmental horticulture. Publication date: June 1990. Reviewed: August 1994. Revised June 2005.